ANALISIS KESESUAIAN NILAI LAHAN TERHADAP ZONA NILAI TANAH BERDASARKAN DISTRIBUSI HARGA PASAR DI KECAMATAN SEPAKU - Widyantoro, Bimo Aji; Membala, Sarah; Adhar, Khairunnisa; Sulistyawati, Tri; William, James (Jurusan Teknik Perencanaan Wilayah dan Kota, Fakultas Sains dan Teknologi, Universitas Islam Negeri Alauddin Makassar, 2026)
Mapping of Land Value Zones (ZNT) requires modelling based on regional factors and validation against actual market prices. The current development of ZNT faces challenges such as uneven market data availability and the need for models capable of comprehensively representing the influence of spatial characteristics. This study aims to analyse the suitability between land values generated through Spatial Multi-Criteria Analysis (SMCA) and the distribution of land market prices interpolated using Inverse Distance Weighting (IDW) in Sepaku District. The SMCA model was constructed using physical environmental variables, land use, accessibility, and proximity to facilities, each classified and scored from 1 to 5. Meanwhile, market price data were obtained through field surveys at 286 spatially distributed sample points and modelled into a continuous surface using the IDW interpolation method within a Geographic Information System (GIS). Suitability analysis was carried out using an overlay approach to measure the degree of spatial alignment between the land value model and the market price distribution. The results show that the ‘suitable’ category covers an area of 762.83 km², the ‘moderately suitable’ category 3,090.79 km², and the ‘not suitable’ category 3,307.09 km². The findings indicate that the alignment between land values and ZNT based on market prices is still influenced by accessibility and the presence of supporting facilities. Therefore, an approach to updating ZNT based on real spatial dynamics is needed to improve the accuracy of spatial planning and land-use policy.